Y-mer: a k-mer based method for determining human Y chromosome haplogroups from ultra-low sequencing depth data - Tarmo Puurand; Märt Möls; Lauris Kaplinski; Kadri Maal; Kaarel Krjutskov; Andres Salumets; Toomas Kivisild; Maido Remm (Genome Biology)
Abstract Determining genetic ancestry of an individual is challenging from poorly preserved or mixed samples that permit only ultra-low coverage sequence at depths less than 0.1 × at target loci. Leveraging recent advances in telomere-to-telomere sequencing of whole genomes with long reads, we develop a new k-mer based method, Y-mer, and show how information from hundreds of thousands of k-mers in distance-based models enables accurate inference of chrY haplogroup from whole-genome sequence at depth less than 0.01x. We test the performance of Y-mer on ancient DNA and prenatal screening data, showing its potential for genetic ancestry inference for cell-free, forensic and ancient DNA research.